Some Tillage-Induced Differences in the Macroaggregates-Size Fraction - Ali Isildar, A.; Akgul, Mesut; Basayigit, Levent (Asian Journal of Chemistry, 2010)
Tillage is one of the most significant management applications that determine properties of the soil aggregates. The effects of three tillage systems on organic carbon and extractable potassium contents of macroaggregates were studied. In the years 2003 and 2004, the soil samples were taken from an experimental pot that has been carried out for four years in a loam soil (typic Xerofluvent). Treatments consisted of three planting systems (chisel plowing, chisel plowing and disc harrowing and chisel plowing and combine harrowing) under the rotation system (sunflower/barle/hungarian vetch and triticale) with three replications. Samples were sieved to separate the five macroaggregate size fractions (8–4.76, 4.76–2, 2–1, 1–0.5, and 0.5–0.25 mm). The differences in the organic carbon and extractable potassium contents of the macroaggregate size fractions were most significant and were independent of the tillage systems. The greatest organic carbon contents were in the > 2 mm macroaggregate size fractions. Extractable potassium content generally increased as macroaggregate size increased. Both mean organic carbon and extractable potassium contents were the greatest in the chisel plowing, the contents of macroaggregate size fractions would not fully show differences among tillage treatments.